Mountain Ultra-Marathon (UTMB) Impact on Usual and Emerging Cardiac Biomarkers - Le Goff, Caroline; Gergelé, Laurent; Seidel, Laurence; Cavalier, Etienne; Kaux, Jean-François (Frontiers in Cardiovascular Medicine, 2022)
The number of participants in ultra-marathons is increasing. However, the data regarding the impact of this type of exercise on the cardiovascular system are contradictory. In our study, 28 ultra-trail runners were enrolled. Blood samples were collected at 3 time points: immediately before, immediately after, and seven days after the ultra-marathon. Different biomarkers were measured. Immediately after the race, the blood concentrations of the different cardiac and inflammatory biomarkers increased significantly. Interestingly, some biomarkers remained high even after seven days of recovery.